Perceptions of Cardiac Rehabilitation Participants Regarding their Health Behaviors and Information Needs during the COVID-19 Pandemic in Brazil - Ghisi G.L.M. (2022)
© 2022, Sociedade Brasileira de Cardiologia. All rights reserved.Background: COVID-19 has impacted how people receive health care for many conditions, including cardiovascular diseases. Objectives: To examine perceptions of cardiac rehabilitation (CR) participants regarding their health behaviors and information needs during the COVID-19 pandemic in Brazil. Methods: In this cross-sectional study, a 27-item questionnaire, developed by the investigators, was administered online to participants from two CR programs. Questions included health literacy (HL; using the Brief Health Literacy Screening Tool), technology use, perceptions before and during the COVID-19 pandemic, and information needs. Pearson correlation coefficients, paired t-tests, and ANOVA were used as appropriate. P < 0.05 was considered statistically significant for all tests. Results: Overall, 159 (25.5%) CR participants answered the questionnaire. Of these, 89.9% had limited or marginal HL and 96.2% reported having internet access at home. Patients are mainly concerned about their family’s health and their own, as well as how the coronavirus is dangerous to their health and how it has changed their lifestyle. Participants perceived that the quality of their health behaviors significantly decreased during the pandemic. The pandemic also changed information needs of CR participants as new needs emerged, such as the control of anxiety levels, staying motivated to live healthily during a pandemic, and how COVID-19 can impact their health condition. Participants with adequate HL significantly perceived the severity of the disease and having access to information significantly more than those with limited HL. Conclusions: Our results highlighted the impact of the pandemic on CR participants’ perceptions regarding their health behaviors and information needs, which can be influenced by HL levels.